Potential Properties of Guabiroba (Campomanesia xanthocarpa O. Berg) Processing: A Native Brazilian Fruit - Amanda A. Prestes; Cristiane V. Helm; Erick A. Esmerino; Ramon Silva; Adriano G. da Cruz; Elane S. Prudencio (Advances in Food Technology and Nutrition Sciences, 2022)
Guabiroba (Campomanesia xanthocarpa O. Berg) is a native Brazilian fruit with an important nutritional value and a great economic potential for processing. This fruit is a source of fibers, carbohydrates, potassium, and bioactive compounds, such as polyphenols, carotenoids, and Vitamin C. The phytochemicals of guabiroba are elucidated regarding their high antioxidant activity, which is related to human health benefits when introduced into a dietary routine. In addition, the antioxidant property of this native fruit can act as a natural preservative against oxidative and enzymatic reactions, and microbiological spoilage, extending the shelf-life of food. Thus, the addition of guabiroba in the development of new products, in addition to improving the functionality of the food, can reduce the use of chemical additives. Studies related to encouraging the use of guabiroba in food formulation, as well as the use of emerging technologies in the processing of this native fruit, become the basis of this review that aims to expand the knowledge of this Brazilian fruit and enhance its application in the food industry.